Issue in building construction due to quality control and quality assurance in Malaysia - Muhammad Fakhri, Mad Din (2019)
The problem in building construction due to quality control &quality assurance are common issue in Malaysia. Common type of includes lack of proper contractor supervision of the work, poor or lack of quality procedure, no quality system, lack of project auditing, using low quality materials, not complete drawing and specification, design complexity, poor availability of required resources and no quality department. Besides that, late design concept and poor performance, lack of quality tools and techniques also will occur of quality issue in building construction. This research objective is to identify the main factor of issue in building construction due to quality control &quality assurance in Malaysia and identify the best solution to overcome the issue in building construction due to quality. Based on a combination of literature review and questionnaire surveys, this paper explores the issue in building construction due to quality control & quality assurance in Malaysia and possible reducing method to minimize the issue, and also the relationship between measures identified with the factors. A quantitative research was conducted by sending sets of questionnaire and got about 105 number of respondents. The results from 101 sets of completed questionnaire were used for the quantitative analysis. In this research shown that the highest ranked for the issue in building construction due to quality control &quality assurance is using low quality materials and zero durability for improper installations in construction will raise the issue. Then, poor performance, lack of quality tool and techniques, not having quality procedures, without auditing project, complex design or lack of quality design, poor in availability of required resources, and no quality department also will cause occur of issue on quality. The most significant solution of issue in building construction due to quality control &quality assurance is government need to terminate or sue contractor where did not follow the specification and standard of procedure protection of the interest of the purchasers. In conclusion, this issue would be important to identify and should minimize the issue in building construction due to quality control & quality assurance in Malaysia.